2016
DOI: 10.1111/caje.12224
|View full text |Cite
|
Sign up to set email alerts
|

What drags and drives mobility? Explaining Canada's aggregate migration patterns

Abstract: Using census data at the economic region level from 1991 to 2006 and a gravity model framework, this paper examines the factors that influence migration within Canada. Results from both Poisson pseudo-maximum likelihood and negative binominal regression models suggest that provincial borders are statistically significant barriers to migration but the magnitude of their effect varies by model specification. The regression results also indicate that differences in employment rates, household incomes and language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…However, the model rejects unemployment as a significant determinant and suggests a negative relationship between weighted migration and capital investment. This result is contrary to empirical findings in the literature, suggesting unemployment rate is an important interprovincial determinant (Coulombe, 2006;Amirault, D., de Munnik, D., & Miller, S., 2012;Day & Winer, 2006;Foot & Milne, 1984).…”
Section: Data and Indicatorscontrasting
confidence: 99%
See 4 more Smart Citations
“…However, the model rejects unemployment as a significant determinant and suggests a negative relationship between weighted migration and capital investment. This result is contrary to empirical findings in the literature, suggesting unemployment rate is an important interprovincial determinant (Coulombe, 2006;Amirault, D., de Munnik, D., & Miller, S., 2012;Day & Winer, 2006;Foot & Milne, 1984).…”
Section: Data and Indicatorscontrasting
confidence: 99%
“…Amirault et al 2012explore Canadian migration by using intra-provincial data (not common in the literature). Using a gravity model, the authors substantiate past results by finding that differences in employment rate, household income, and language are important in explaining migration (Amirault et al, 2012). More significantly for policy formulation, the authors found that provincial borders pose a statistically significant obstruction to interprovincial mobility, with the predominance of Canadian migration occurring intra-provincially (Amirault et al, 2012).…”
Section: Examination Of the Literaturesupporting
confidence: 69%
See 3 more Smart Citations